Therapeutic protein deimmunization by T‐cell epitope removal: antigen‐specific immune responses in vitro and in vivo. Issue 6 (18th April 2017) - Asgari, Saeme; Ebrahim‐Habibi, Azadeh; Mahdavi, Mehdi; Choopani, Mohammad; Mirzahoseini, Hasan
Abstract : Hirudin III is an effective anti‐coagulant; however, in 40% of treated patients, a high‐titer of anti‐Hirudin III IgG antibodies is observed. Development of antibody responses requires the activation of helper T lymphocyte (HTL), which is dependent on peptide epitopes binding to HLA class II molecules. Based on computational prediction softwares, four new mutants of Hirudin III, T4K, S9G, V21G, and V21K, had been designed with the aim of reducing the binding affinity of these HTL epitopes. The constructed mutants have been purified and assayed for bioactivity. Finally in vitro and in vivo cell‐mediated responses were assessed and humoral immune assays were performed. All modified forms of Hirudin III were active, and showed significantly reduced human T‐cell responses. All mutants indicated lower human IFN‐γ level compared to native Hirudin, and V21K indicated lowest IFN‐γ level. Mice immunized with T4K and V21K showed a significant reduction in total antibody responses and mouse IFN‐γ levels. Mice immunized with V21K after 3rd immunization had lower T‐cell proliferation compared to native Hirudin and other mutants. Based on these results, V21K is proposed as the best alternate Hirudin III candidate with lowest antigenicity. These findings validate our rational design strategy aimed at providing new active analogs of therapeutic proteins with reduced immunogenicity.